RELATIONS, STRUCTURE, VALUES AND NORMS IN THE SOCIETY OF THE TARGET INDUSTRY IN KAMPUNG SASIRANGAN, BANJARMASIN CITY - melly agustina permatasari; Puji Hardati (JURNAL SOCIUS, 2021)
The purpose of this study was to identify and analyze (1) relations, (2) structures, (3) values, and (4) norms in the Sasirangan industrial community in Sasirangan Village. The research location is in Sasirangan village, Banjarmasin city, South Kalimantan. This research uses a qualitative approach. The subject of community research in Sasirangan Village. The research informants were craftsmen, traders and buyers. Data collection techniques are carried out through observation, interviews, and documentation. The research focuses on social relations (Gillin and Gillin), social structure (Linton Ralph), values (Koentjaraningrat) and norms (Soerjono Soekanto). The data analysis technique starts from data reduction, data display/presentation, and verification/conclusion. The data credibility test was carried out by extending observations, increasing persistence, member checking and triangulation. The results showed that social relations include the relationship between individuals and themselves, individuals with families, individuals with institutions, individuals with communities, individuals with society, and individuals with the nation; in the form of cooperation, competition and accommodation. The social structure includes governors, mayors, heads of RT / RW, craftsmen and sasirangan sellers. The values that exist in society include economic, social and environmental values as well as the cultural values of the Banjar. The norms in society are related to the philosophy of life of the Banjar ethnic group, namely baiman, bauntung, cangkal, haram manyarah waja to kaputing, as well as behavior in everyday life.